Investigation of the optimal condition for the growth and biofilm development of Candida albicans on three dental materials - Hoai Thu Le; Truong Thi Luc Phuong; Giang Hoang Huy; Phuoc-Vinh Nguyen; Bac Vu Giang Nguyen (Iranian Journal of Microbiology)
Background and Objectives: Candida albicans as pathogenic fungi cause conditions like oral candidiasis and dental caries. The critical role of biofilms in the pathogenicity of C. albicans necessitates the exploration of conditions that promote their growth and development. Our study aimed to delineate the optimal conditions conducive to the proliferation and biofilm production of C. albicans on prevalent dental materials. Materials and Methods: To approximate oral cavity conditions, culture media were enhanced with various glucose concentrations to assess the growth and biofilm-forming capability of the fungus through growth curve analysis and crystal violet assays. Results: The findings suggest that YPG medium augmented with 4% glucose presents as an optimal environment for C. albicans growth. Biofilm formation was most effectively promoted in RPMI medium supplemented with the same concentration of glucose. Composite resin was identified as the substrate most susceptible to biofilm development by C. albicans under these conditions. Conclusion: This investigation highlights the necessity of accounting for microbial activity and material characteristics in the prevention and management of dental biofilm formation. Our research advances the understanding of in vitro cultivation of C. albicans, simulating the oral milieu more accurately and contributing to enhanced oral health management for individuals utilizing temporary dental fixtures.